2021
DOI: 10.1142/s0192415x21500804
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin Attenuates Palmitic Acid-Induced Inflammation and Apoptosis of Vascular Endothelial Cells through Mediating PI3K/Akt/eNOS Signaling Pathway

Abstract: A well-known medicinal mushroom in the field of traditional Chinese medicine, Cordyceps sinensis, is a rare natural-occurring entomopathogenic fungus, and it typically grows at high altitudes on the plateau of the Himalayan. Previous studies indicated that cordycepin, the main bioactive chemical of Cordyceps sinensis, has very potent anticancer, anti-oxidant and anti-inflammatory activities. However, its protective effects against atherosclerotic changes in vascular endothelial cells have not been fully elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Furthermore, BER reduces the excessive production of mitochondrial ROS by activating the PGC-1α signaling pathway, which supports mitochondrial energy balance [74]. Additionally, COR has also been demonstrated to reduce ROS levels [66,75], due to the increased activity of SOD and CAT [76]. Furthermore, the ROS level of the NMN group was dramatically lower compared to both the BER group and COR group, which was due to the better capability of NMN to regulate the mRNA expression levels of antioxidant genes (Figure 3C).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, BER reduces the excessive production of mitochondrial ROS by activating the PGC-1α signaling pathway, which supports mitochondrial energy balance [74]. Additionally, COR has also been demonstrated to reduce ROS levels [66,75], due to the increased activity of SOD and CAT [76]. Furthermore, the ROS level of the NMN group was dramatically lower compared to both the BER group and COR group, which was due to the better capability of NMN to regulate the mRNA expression levels of antioxidant genes (Figure 3C).…”
Section: Discussionmentioning
confidence: 93%
“…It was reported that 6-gingerol alleviates intracellular ROS in HepG2 cells caused by patulin [ 50 ] and lipopolysaccharide (LPS) [ 51 ]. A previous study reported that PA could cause an increase in intracellular ROS levels [ 52 ]. However, it was not clear about the effect of 6-gingerol on PA-induced intracellular ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of palmitic acid on endothelial cells, smooth muscle cells and macrophages is able to induce the high-fat model in vitro ( 14 , 15 ). Palmitic acid may lead to inflammation and apoptosis of vascular endothelial cells by mediating the PI3K/Akt/endothelial nitric oxide synthase signaling pathway ( 16 ). Palmitic acid induced endothelial lipotoxicity and lectin-like oxidized LDL receptor-1 upregulation by reducing endoplasmic reticulum stress in HUVECs.…”
Section: Discussionmentioning
confidence: 99%